RECENT SYSTEMATIC REVIEW ON ORGANIZATIONAL CULTURE IN HIGHER EDUCATION INSTITUTIONS (HEIS) - Abdullah, Cik Othman; Abd. Wahat, Nor Wahiza; Anuar, Mohd Ashraff Mohd (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This systematic literature review explores the evolving landscape of organizational culture in higher education institutions (HEIs), aiming to understand its multifaceted impact on institutional dynamics and performance. In recent years, organizational culture has garnered increasing attention in higher education due to its critical role in shaping employee behavior, leadership effectiveness, and overall institutional success. However, there is limited consolidated insight that holistically maps the scope of current findings in this domain. To address this gap, we conducted an advanced systematic search using the Scopus and Web of Science (WoS) databases, guided by the PRISMA framework. The search strategy employed key terms such as "organizational culture," "workplace culture," and "higher education institution," resulting in a final dataset of 40 peer-reviewed articles. Through rigorous screening and thematic synthesis, three core themes were identified: (1) Organizational Culture and Employee Outcomes, which highlights how workplace culture influences motivation, engagement, and performance; (2) Organizational Culture, Leadership, and Institutional Performance, emphasizing the interconnection between leadership styles and cultural alignment in driving institutional effectiveness; and (3) Organizational Culture Typologies, Structures, and Academic Environment, which examines various cultural models, governance structures, and their implications for teaching and research ecosystems. The review reveals that a strong, well-aligned organizational culture positively correlates with improved employee satisfaction, leadership cohesion, and institutional performance. In conclusion, the study provides a comprehensive synthesis of current literature, offering valuable insights for policymakers, academic leaders, and researchers seeking to cultivate effective organizational cultures within higher education institutions.